Peran Faktor Determinan Sosial Kesehatan, Personal Hygiene, dan Lingkungan dalam Penularan Protozoa Usus - Khuluq, Muhammad Khusnul; Irawati, Nur Ayu Virginia; Mutiara, Hanna; Suwandi, Jhons Fatriyadi (Medula, 2025)
Intestinal protozoan infections are a significant health issue, particularly in developing countries with low socioeconomic conditions, poor sanitation, and inadequate personal hygiene practices. The transmission of intestinal protozoa is closely linked to various social determinants of health, including education level, occupation, and household income. Parents with lower education levels tend to have limited knowledge about hygiene and infection prevention, increasing the risk of transmission to children. Certain occupations, such as farming, are also associated with a higher risk of infection due to exposure to contaminated environments. Personal hygiene plays a crucial role in preventing intestinal protozoan infections. Habits such as washing hands before eating, after defecation, and maintaining overall cleanliness can reduce the risk of transmission through the fecal-oral route. Additionally, inadequate environmental sanitation, including the absence of toilets, poor waste management, and limited access to clean water, contributes to high infection rates. Several studies indicate that communities living in areas with poor sanitation are more vulnerable to infection, mainly due to high fecal contamination in water and soil. Beyond social and environmental factors, the presence of pets or livestock can also serve as a source of transmission. Animals exposed to intestinal protozoa pose a risk of spreading the infection if not properly managed. Therefore, preventing intestinal protozoan infections requires a comprehensive approach, including health education, increased awareness of personal hygiene, improved sanitation facilities, and access to safe drinking water for communities.